A typical super-heater tube leakage and high temperature corrosion mechanism investigation in a 260 t/h circulated fluidized boiler. (January 2020) - Xiong, Xiaohe; Lv, Zhaomin; Tan, Houzhang; Wei, Bo
Highlights: A typical hot salt corrosion at super-heater in a circulated fluidized boiler was well investigated. Corrosion products present obvious layered structure with Cr concentration. The major compositions in the corrosion products are Fe2 O3, Fe3 O4 and FeCr2 O4 . Abstract: Aiming to explore the high temperature corrosion mechanism in a 260 t/h circulated fluidized boiler, a section of bursting super-heater tube was cut down and the scanning electron microscope relevant characterization analysis was conducted. Results show that the major compositions in the corrosion products are iron oxide such as Fe2 O3, Fe3 O4 and FeCr2 O4 rather than sulfide, occupying a rough 70% mass ratio. The corrosion type is not typical H2 S corrosion but salt corrosion. The sodium sulfate and sodium chloride are both found covered on the super-heater tube surface, but the sodium sulfate is the major corrosion culprit. Line scan results show that the layered structure of two oxidation layers are obviously observed. The chromium is enriched in the inner layer with a depth of 572 μm while the iron is full of the whole oxidation layer with a 1017 μm depth. The chromium oxide layer is compact and can diminish the corrosion rate. The iron oxide layer is loose and porous and can supply the transfer path to the oxygen medium. To alleviate the high temperature corrosion, thermal spay coatings, aluminized steel tube, coal quality control etc. these measures are suggested and put forward.